Impacto da certificação florestal nas condições de trabalho no complexo florestal - Castral, Ana Paula (2003)
This assignment has as aim to analyze the impact of forest certification about the work conditions of forest workers. It s believed that, although the origin of forest certification had been conditioned by market factors, its social worries are producing effect at companies that adopted it. In this assignment will be described the formation of forest complex, reminding the fundamental policies for the consolidation of the current Brazilian complex. It ll also be done a short discussion of the two forest certification systems used in our country: FSC (Forest Stewardship Council) and CERFLOR (The Brazilian Forest Certification System). The assignment advances at the discussion of the forest production process and the organization of work at forest production. In this sense, the contribution of this assignment is to identify the changes at the work organization, occurred after the certification and if improvements at work conditions of forest workers had happened.